Effects of Eight-week Dynamic Neuromuscular Stabilization Exercises on the Static and Dynamic Balance of Educable Mentally Retarded Female Students - Ensie Dehghani; Gholam Ali Ghasemi; Morteza Sadeghi (Ṭibb-i Tavānbakhshī, 2023)
Background and Aims Balance is an important factor in people with intellectual disability to have an independent life. These people are weak static and dynamic balance due to lack of development in their central nervous system, defects in the sensory-motor pathways, and having a sedentary life. This study aims to determine the effect of eight weeks of dynamic neuromuscular stabilization (DNS) exercises on static and dynamic balance of educable mentally retarded female studentsMethods In this study, participants were 26 educable mentally retarded female students aged 15-20 years (Mean age: 17.19±1.50 years, IQ: 61.15±6.07, weight: 58.9±12.73 kg, height: 157.92±6.07 cm) who were selected using purposive and convenience sampling methods and randomly divided into two groups of training (n=13) and control (n=13). Before and after training, their static balance and dynamic balance on the right and left feet were evaluated using a foot scan device. Subjects in the training group performed DNS exercises at 24 sessions, each session for 40 minutes. No intervention was provided to the control group; they performed their routine activities. Repeated measures analysis of variance was used to analyze the data. The significance level was set at 0.05.Results After eight weeks of DNS exercises, the results showed a significant improvement in static balance (F=72.54, P=0.001), dynamic balance on the right foot (F=90.90, P=0.002) and dynamic balance on the left foot (F=61.58, P=0.001) in the training group compared to the pretest scores and compared to the control group.Conclusion DNS exercises can be used as an effective method to improve static and dynamic balance of educable mentally retarded female students.